Application of trichloroisocyanuric acid in controlling kiwifruit bacterial canker disease demonstrates its promising potential as an eco-friendly bactericide - Jianyou Gao; Jiewei Li; Cuixia Liu; Hongjuan Gong; Beibei Qi; Rongxiang Zhu; Liming Xia; Li Li; Shibiao Liu; Qiaosheng Jiang; Kaiyu Ye; Faming Wang (Chemical and Biological Technologies in Agriculture)
Abstract The growing concerns over food safety have intensified calls for alternatives to toxic pesticides in agriculture. Despite these concerns, the global agricultural industry remains heavily reliant on chemical pesticides to maintain crop yields. However, the overuse of these chemicals has resulted in significant biodiversity loss and environmental degradation, highlighting the urgent need for safer, non-toxic, and sustainable alternatives. Trichloroisocyanuric acid (TCCA), a cost-effective and relatively safe industrial oxidant commonly used for disinfection, has shown potential for plant disease management. However, its application in this context remains largely unexplored. In this study, we evaluate the efficacy of TCCA in controlling Pseudomonas syringae pv. actinidiae (Psa), the causative agent of bacterial canker in kiwifruit, and explore its underlying mechanisms of action. Our results demonstrate that TCCA effectively inhibits Psa growth in vitro, even at low concentrations, with minimum inhibitory concentrations (MICs) of 20 mg/L (TCCA added directly to the Psa suspension) and 100 mg/L (Psa cells mixed with liquid LB medium before adding TCC). In vivo, TCCA treatment at a concentration of 500 mg/L substantially reduced Psa colonization on both kiwifruit leaves and canes, outperforming conventional bactericides such as copper hydroxide, chlorothalonil, and ethylicin, as well as alternative treatments like pyraclostrobin-dysonline and Xinjunan acetate. Mechanistic investigations revealed that TCCA inhibited bacterial biofilm formation, impaired motility, disrupted cell integrity, and suppressed the expression of virulence-related genes, ultimately leading to bacterial cell death. Additionally, TCCA treatment of both healthy and infected canes induced the activity of key defense-related enzymes, including catalase (CAT), peroxidase (POD), glutathione reductase (GR), and phenylalanine ammonia-lyase (PAL), suggesting that TCCA may activate systemic plant defense responses. These findings position TCCA as a promising, environmentally friendly alternative to traditional toxic bactericides, offering a sustainable and effective solution for plant disease management with reduced ecological risks. Graphical Abstract